Coagulase-Negative Staphylococci in Human Milk From Mothers of Preterm Compared With Term Neonates. (May 2017) - Soeorg, Hiie; Metsvaht, Tuuli; Eelmäe, Imbi; Metsvaht, Hanna Kadri; Treumuth, Sirli; Merila, Mirjam; Ilmoja, Mari-Liis; Lutsar, Irja
Background: Human milk is the preferred nutrition for neonates and a source of bacteria. Research aim: The authors aimed to characterize the molecular epidemiology and genetic content of staphylococci in the human milk of mothers of preterm and term neonates. Methods: Staphylococci were isolated once per week in the 1st month postpartum from the human milk of mothers of 20 healthy term and 49 preterm neonates hospitalized in the neonatal intensive care unit. Multilocus variable-number tandem-repeats analysis and multilocus sequence typing were used. The presence of the mecA gene, icaA gene of the ica -operon, IS 256, and ACME genetic elements was determined by PCR. Results: The human milk of mothers of preterm compared with term neonates had higher counts of staphylococci but lower species diversity. The human milk of mothers of preterm compared with term neonates more often contained Staphylococcus epidermidis mecA (32.7% vs. 2.6%), icaA (18.8% vs. 6%), IS 256 (7.9% vs. 0.9%), and ACME (15.4% vs. 5.1%), as well as Staphylococcus haemolyticus mecA (90.5% vs. 10%) and IS 256 (61.9% vs. 10%). The overall distribution of multilocus variable-number tandem-repeats analysis (MLVA) types and sequence types was similar between the human milk of mothers of preterm and term neonates, but a few mecA -IS 256 -positive MLVA types colonized only mothers of preterm neonates. Maternal hospitalization within 1 month postpartum and the use of an arterial catheter or antibacterial treatment in the neonate increased the odds of harboring mecA -positive staphylococci in human milk. Conclusion: Limiting exposure of mothers of preterm neonates to the hospital could prevent human milk colonization with more pathogenic staphylococci.